CONCENTRATION OF SOLUBLE SALTS IN COOLING WATER OF POWER PLANTS WITH BLOW DOWN RECIRCULATION - Kochmarskii, Volodymyr; Kostiuk, Oleksandr; Filipovych, Yurii (WATER AND WATER PURIFICATION TECHNOLOGIES. SCIENTIFIC AND TECHNICAL NEWS, 2021)
The method for calculating the dynamics of concentration of soluble salts (tracers) using the assumption of their homogeneous distribution in the water volume of the circulated cooling system (CCS) under the conditions of recirculation of part of the purge water was proposed. The assumption of homogeneity of salt distribution is substantiated by the fact that the period of mixing of cold water (CW) in CCS is equal to several hours, and the period of setting the concentration limits is calculated in tens of days. In this approximation the law of change of concentration of tracers in time from the moment of their supply in CCS in modes without and with recirculation of a part of purge water and without any processing is received. It is shown that without recirculating treatment, recirculation of purge water increases the maximum salt concentration and the time to reach it. Attention is drawn to the fact that the flow rate consists of two parts: controlled and uncontrolled. When calculating the allowable amount of purge recirculation, it is necessary to use the value of the total purge flow. It is important to understand that the relative change in total purge is always less than the controlled one. To obtain the cost of full purge, it is necessary to calculate its uncontrolled part. The procedure for calculating the uncontrolled purge is given in the paper. Since there are restrictions for of maximum allowable concentration (MAC) on the concentrations of tracers in the CCS, the expressions obtained in this work are consistent with the requirements of the MAC and allow for a given degree of concentration of salts φ, to calculate the limit of recirculation flow. It is shown that the recirculation regime can be applied without additional measures for CCS with a low initial degree of salt concentration and low concentration in the feed water. The proposed algorithm is used to predict the results of recirculation in the case of a specific CСS for thermal power plants with an electrical capacity of 1200 MW and the ratio CMAC/C0 = 5. It is shown that in this case recirculation has significant economic and environmental effects. However, at high, concentrations of tracers C0, compared to MAC, feed water recirculation is meaningless. The calculation algorithm applies to tracers, i.e. salts that do not give deposits, but only limited by the MAC requirements and the risk of corrosion or environmental considerations. Therefore, the above technique cannot be directly used for sparingly soluble salts, such as calcium carbonate. In this case, it requires significant correction. Note the convenient use in calculations of the earlier introduced by us concept of regime (dynamic) factor φ, especially when comparing the real consumption of the main flows of ССS to calculated and in determining the evaporative capacity of cooling towers, or assessing the degree of salt concentration.